The Tahlilan Tradition as a Fringe Sufism Movement - Siti Fatimah; Ulfa Masamah; Isti Choriyah (Javanologi: International Journal of Javanese Studies, 2023)
AbstractJavanese society in which Bangunrejo Kidul Kedunggalar Ngawi Village has social, cultural, and religious traditions. Tradition is one of the inherent cultures and becomes a habit of min to think and act the people of Bangunrejo Kidul Village. One tradition that is still maintained today is the tahlilan tradition. This tradition became a fringe sufism movement that influenced the religious practice of the community both habl min Allah and habl min nass. This research is qualitative, using the case study method with a naturalistic approach because the object raised is the tahlilan tradition that exists among Nahdliyin residents, especially in Bangunrejo Kidul Village and the approach uses religious sociology. The tahlilan tradition is one of the religious cultures that is still maintained and practiced by the people of Bangunrejo Kidul Village, especially Nahdliyin as a medium of da'wah to build a balance of personal piety to increase faith in Allah Almighty and social piety in the form of harmony and social harmony. The tradition of tahlilan as a fringe urban sufism movement that indirectly teaches taqarub ila Allah by strengthening religious messages, increasing religious knowledge, and strengthening other religious values. In its development, the tradition of tahlilan experienced an expansion of functions not only identical to death but also in it there was a process of good habituation in all religious activities and passed down from generation to generation. Keywords: tahlilan tradition, da'wa, nahdliyin, village community, prayer of salvation